The uptake of converged in newsroom platforms in Zimbabwe : a case study of media centre from 2016 to date - Mugidwa, Marceline M (Midlands State University, 2020)
The study explored the uptake of converged newsroom platforms in Zimbabwe focusing on Media Centre from 2016 to date. The study aimed to explore the uptake of a converged newsroom platforms in Zimbabwe focusing on Media Centre from 2016 up to date; determine how converged newsroom platforms enhance democracy and free circulation of news across the globe; and establish how converged newsroom platforms lead to multitasking while enforcing professionalism. The study was qualitative in nature and data was collected from targeted population through interviews, questionnaires and participant observation. Furthermore, the study employed convenience and purposive sampling techniques that are purely qualitative. The study was also guided by three theories namely social network site theory, the virtual sphere revisited and critical theory of technology. The findings were analysed using critical discourse and also presented. The study deduced that Media Centre engages in activities like streaming of press conferencing, posting videos and texts on their online platforms. Newsroom convergence has brought changes to audience since they operate differently from traditional media which is not accommodating. The study also deduced that converged newsroom platforms enhance the digital public sphere and democracy in Zimbabwe. The researcher recommended MC to put extra effort in covering issues affecting marginalised communities like they do in covering issues in towns, press conference fee for less privileged people should be open for negotiation and that MC should be partial and avoid being a Civil Society organisation during the day and political players by night.